Annual Research Review: Secular trends in child and adolescent mental health. (12th December 2014) - Collishaw, Stephan
<x xml:space="preserve">Abstract</x> Background Child and adolescent mental health problems are common, associated with wide‐ranging functional impairments, and show substantial continuities into adult life. It is therefore important to understand the extent to which the prevalence of mental health problems has changed over time, and to identify reasons behind any trends in mental health. Scope and Methodology This review evaluates evidence on whether the population prevalence of child and adolescent mental health problems has changed. The primary focus of the review is on epidemiological cross‐cohort comparisons identified by a systematic search of the literature (using the Web of Knowledge database). Findings Clinical diagnosis and treatment of child and adolescent psychiatric disorders increased over recent decades. Epidemiological comparisons of unselected population cohorts using equivalent assessments of mental health have found little evidence of an increased rate of ADHD, but cross‐cohort comparisons of rates of ASD are lacking at this time. Findings do suggest substantial secular change in emotional problems and antisocial behaviour in high‐income countries, including periods of increase and decrease in symptom prevalence. Evidence from low‐ and middle‐income countries is very limited. Possible explanations for trends in child and adolescent mental health are discussed. The review also addresses how cross‐cohort comparisons can provide valuable complementary information on the aetiology of mental illness.